Hypocholesterolemic effects of mevinolin in patients with heterozygous familial hypercholesterolemia. - Illingworth, D R (1984)
We have evaluated the hypolipidemic effects of mevinolin, a competitive inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase, the rate-limiting enzyme in cholesterol biosynthesis in 13 patients with heterozygous familial hypercholesterolemia (FH). Patients were maintained on a low-cholesterol diet and received sequentially increasing doses of 5, 10, 20, and 40 mg of mevinolin twice daily for a period of 1 mo on each dose. Plasma concentrations of low density lipoprotein cholesterol decreased by 19.8% on the 5 mg twice daily dose (P less than 0.05 vs. base line), 28.4% on 10 mg of mevinolin twice daily (P less than 0.05 vs. 5 mg twice daily), 35% on 20 mg of mevinolin twice daily (P less than 0.05 vs. 10 mg twice daily), and 37.7% on 40 mg of mevinolin twice daily (not statistically different from 20 mg twice daily). Concentrations of high density lipoprotein cholesterol remained stable on all doses of mevinolin whereas plasma triglyceride levels fell significantly on the 20 mg (-30.7%) and 40 mg (-34.3%) twice daily doses of mevinolin. Mevinolin was well tolerated and all patients completed the study period. Side effects during the period of study were limited to transient insomnia and headaches in two patients, transient increases in alkaline phosphatase in three patients, and a modest but sustained increase in alkaline phosphatase in a fourth patient. These results indicate that mevinolin is an effective hypolipidemic agent in patients with heterozygous FH but that the optimal doses in these patients are greater than those previously reported in normal volunteers. If long-term safety can be satisfactorily established, mevinolin offers considerable promise in the therapy of heterozygous FH.